2017
DOI: 10.2147/cia.s133838
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of power and resistance exercises on hemodynamic measurements of older women

Abstract: PurposeThe purpose of this study was to compare the acute effects of resistance training (RT) and power training (PT) on the hemodynamic parameters and nitric oxide (NO) bioavailability of older women.Materials and methodsA randomized experimental design was used in this study. Twenty-one older women (age: 67.1±4.6 years; body mass index: 28.03±4.9 kg/m2; systolic blood pressure: 135.1±21.1 mmHg) were recruited to participate in this study. Volunteers were randomly allocated into PT, RT, and control session (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 36 publications
3
41
3
2
Order By: Relevance
“…That study [10] found a longer post-exercise hypotension response after 70% of 1RM condition compared with the 80% of 1RM condition. With fewer sets performed to repetition failure at the lowest intensity, there might have been less predominance of the sympathetic nervous system during and after the 70% of 1RM condition [25]. Thus, it seems from this study that the 90% or 95% of 1RM condition involved the right trade-off between less sympathetic nervous system activation to stimulate the longest duration of a reduction in post-exercise blood pressure in Paralympic powerlifting athletes.…”
Section: Discussionmentioning
confidence: 67%
“…That study [10] found a longer post-exercise hypotension response after 70% of 1RM condition compared with the 80% of 1RM condition. With fewer sets performed to repetition failure at the lowest intensity, there might have been less predominance of the sympathetic nervous system during and after the 70% of 1RM condition [25]. Thus, it seems from this study that the 90% or 95% of 1RM condition involved the right trade-off between less sympathetic nervous system activation to stimulate the longest duration of a reduction in post-exercise blood pressure in Paralympic powerlifting athletes.…”
Section: Discussionmentioning
confidence: 67%
“…In fact, just recently, in a seminal experiment from our laboratory, the acute effects of PT with elastic bands in blood pressure values of normotensive and hypertensive older adults were elucidated ( Coelho-Junior et al, 2017a ). Results demonstrate a significant PEH during 35 min after exercise cessation ( Coelho-Junior et al, 2017a ). Therefore, data of the present study showed, for the first time, that hypotension post PT can be—at least, partially—preserved during the subsequent performance of ADL.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, possible mechanisms associated with the protective effects of PT in blood pressure values were not investigated in the present study. However, data from Coelho-Junior et al (2017a) indicate that nitric oxide (NO) bioavailability is increased during 1 hr after a unique session of PT in older women. These data have been also demonstrated by other studies, so that is possible infer that this molecule collaborates with the effects of PT observed in the present study ( Asano et al, 2013 ; Asano et al, 2014 ; Santana et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations